Insights on the development and clinical implications of internal jugular vein anomalies – A report on fenestrated internal jugular vein encountered during neck dissection (Indian Journal of Case Reports, 2025)
In this fascinating clinical report, we explore the case of a 70-year-old male patient diagnosed with T2N1MO squamous cell carcinoma of the lip at the otolaryngology department. Diagnostic imaging before surgery unveiled an intriguing anomaly involving fenestration of the internal jugular vein (IJV), adding a layer of complexity to the surgical plan. With careful preparation, our surgical team skilfully executed a wide local excision of the primary tumor and performed a modified radical neck dissection, complemented by Abbe Estlander flap reconstruction. Identifying this rare IJV anomaly preoperatively enabled meticulous planning, allowing our team to navigate with precision, safeguarding nearby nerves and blood vessels. This exceptional case underscores the importance of recognizing anatomical variations during intricate procedures such as neck dissections. Through this report, we elucidate the pre-operative suspicion, intraoperative identification, and successful management of this rare IJV fenestration encountered during a challenging neck dissection.